2017
DOI: 10.5194/acp-17-9797-2017
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up aerosol–cloud closure: towards understanding sources of uncertainty in deriving cloud shortwave radiative flux

Abstract: Abstract. Top-down and bottom-up aerosol–cloud shortwave radiative flux closures were conducted at the Mace Head Atmospheric Research Station in Galway, Ireland, in August 2015. This study is part of the BACCHUS (Impact of Biogenic versus Anthropogenic emissions on Clouds and Climate: towards a Holistic UnderStanding) European collaborative project, with the goal of understanding key processes affecting aerosol–cloud shortwave radiative flux closures to improve future climate predictions and develop sustainabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 62 publications
(96 reference statements)
0
32
0
Order By: Relevance
“…Moore et al (2013) summarised 36 previous studies of CCN closure and similarly found that CCN concentrations were generally overpredicted, other than when using size-resolved measurements of aerosol composition. Additionally, a previous comparison by Simpson et al (2014) showed that ACPIM calculated higher CDNC compared to simpler parameterisations when using multiple aerosol modes. The values of modelled CDNC using the representative morning and afternoon updrafts are between the 75th and 90th percentiles of measured CDNC shown in Fig.…”
Section: Model Resultsmentioning
confidence: 93%
“…Moore et al (2013) summarised 36 previous studies of CCN closure and similarly found that CCN concentrations were generally overpredicted, other than when using size-resolved measurements of aerosol composition. Additionally, a previous comparison by Simpson et al (2014) showed that ACPIM calculated higher CDNC compared to simpler parameterisations when using multiple aerosol modes. The values of modelled CDNC using the representative morning and afternoon updrafts are between the 75th and 90th percentiles of measured CDNC shown in Fig.…”
Section: Model Resultsmentioning
confidence: 93%
“…In tracing the evolution of aircraftbased wind measurements in the atmosphere, three axes of development have been pursued since the 1960s: improvements in airborne platforms, inertial navigation systems (INSs) and sensors. Airborne platforms have evolved from large aircraft (e.g., Canberra PR3, Axford, 1968or NCAR Queen Air, Brown et al, 1983 to ultra-light unmanned aerial systems (e.g., M 2 AV; Spiess et al, 2007). INSs measure linear and rotational motion of the aircraft (or unmanned aerial system) and are used to back out wind vectors in the Earth's coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of aerosol activation is beyond the scope of this analysis and is non-trivial (e.g. Sanchez et al, 2017). Additionally, we have no measurements with which to constrain factors such as the size-dependence of chemical composition and mixing state, which strongly affect the accuracy of CCN closure calculations (Moore et al, 2013), so such an investigation would be purely speculative.…”
Section: Parcel Modellingmentioning
confidence: 99%